PERANCANGAN RENOVASI MASJID PONPES HIDAYATUL QUR’AN UNTUK MENINGKATKAN KUALITAS FASILITAS PENDIDIKAN - TAUFIKKURRAHMAN, TAUFIKKURRAHMAN; WARDANI, LILA KURNIA; RAHAYU, YEKTI SRI (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
This article was written based on a community service program implemented in an effort to improve the quality of educational facilities at the Hidayatul Qur'an Islamic Boarding School Mosque. This Islamic boarding school stands on an area of ??1,342 m2 with a built-up area of ??541 m2. The facilities available for learning are still very minimal and the condition of the mosque building is also old with the condition of the building worrying about its safety. As the number of students continues to increase, foundation management really needs to improve adequate educational infrastructure. However, foundation managers have limited expertise in drawing and designing mosque building renovation designs to improve the quality of educational facilities. This community service aims to provide working drawing documents and budget plans for renovation and construction costs as a basis for implementing the construction of educational facilities. The method used is the science and technology diffusion method. The results of the program implementation produced a product document planning the renovation of the mosque at the Hidayatul Qur'an Blitar Islamic Boarding School. This document in the form of an image design complies with applicable standards and is useful in implementing the construction of educational facilities at the Hidayatul Qur'an Islamic Boarding School mosque. ABSTRAKNaskah ini ditulis berdasarkan program pengabdian kepada masyarakat yang dilaksanakan dalam upaya meningkatkan kualitas sarana pendidikan di Masjid Pondok Pesantren Hidayatul Qur’an. Ponpes ini berdiri pada lahan seluas 1.342 m2 dengan luas terbangun seluas 541 m2. Sarana yang tersedia untuk pembelajaran masih sangat minim dan kondisi bangunan masjid juga sudah tua dengan kondisi bangunan yang mengkhawatirkan keamanannya. Seiring dengan pertambahan jumlah santri yang terus meningkat, pengelola yayasan sangat memerlukan perbaikan sarana prasarana pendidikan yang memadai. Namun demikian pengelola yayasan memiliki keterbatasan keahlian dalam menggambar dan merancang desain renovasi bangunan masjid untuk meningkatkan kualitas fasilitas pendidikan. Pengabdian kepada masyarakat ini bertujuan untuk menyediakan dokumen gambar kerja dan rencana anggaran biaya renovasi serta pembangunan sebagai dasar untuk pelaksanaan pembangunan fasilitas pendidikan. Metode yang digunakan adalah metode difusi iptek. Hasil pelaksanaan program menghasilkan sebuah produk dokumen perencanaan renovasi masjid di Ponpes Hidayatul Qur’an Blitar. Dokumen berupa desain gambar ini sesuai standar yang berlaku dan bernanfaat dalam pelaksanaan pembangunan fasilitas pendidikan di masjid Ponpes Hidayatul Qur’an.